The Roman Family During the Reign of Emperor Augustus (27 BC – 14 AD) - Andisha, Ahmed Mohamed; Al-Qumati, Hamida Oweidat ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2014)
This study explores the structure of the Roman family during the reign of Emperor Augustus (27 BC – 14 AD), focusing on the role of the pater familias (head of the family), who held sovereign authority over all family members under Roman law. The family consisted of the father, wife, unmarried daughters, biological or adopted sons and their households, as well as slaves and freedmen. The father legally owned all family property and had the right to grant portions (peculium) to others, while also possessing the power to issue life-and-death decisions over family members. Over time, Roman law began to intervene to limit the father’s absolute authority and protect family members from excessive abuse. The study draws on historical and legal sources to present a comprehensive view of family dynamics in Roman society during this pivotal period.